Rebrii O. V. Сreative dimensions of translating children’s literature - Rebrii O. V. (Philological Treatises, 2020)
The article is dedicated to analyzing such important aspects of translating children’s literature as communicative-psychological, didactic and cultural. Since the cumulative effect of these factors determines the success in translating children’s literature, the essence of translator’s creativity lies in the ability to combine them seamlessly.